(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Sexual dysfunction in men, a problem that becomes more ubiquitous increasing age, including erectile dysfunction (ED), decreased sexual desire, and ejaculatory disorders. The study was conducted to describe the incidence of sexual dysfunction in men with diabetes, examine the relationship between sexual dysfunction and cardiovascular risk factors, major cardiovascular events in men with diabetes in Quang Nam province in 2024. Methods: Description of a series of diseases, from January 2024 to April 2024 at Northern Mountainous Area General Hospital Northern Quang Nam. Results: We conducted a study on 63 men with diabetes with an average age of 54.4 ± 9.1 years and duration of diabetes 5.1 ± 4.4 years. We recorded that 15.9% of patients did not use hypoglycemic drugs. More than 50% of subjects have cardiovascular risk factors such as overweight, obesity, smoking, and hypertension. The rate of erectile dysfunction was 69.8%, of which up to 20.6% of study subjects were recorded as having moderate-severe ED. Diabetic patients with erectile dysfunction are significantly more likely to have age, waist circumference, HbA1C, fasting blood sugar, blood urea, smoking rate, diabetic neuropathy, coronary artery disease, and hypogonadism when compared to diabetic patients with erectile dysfunction compared with the group without ED. Conclusion: It is essential to get further researches in terms of these above issue that help guide treatment and resolve the existing situation in the group of male patients with diabetes.